The Dimensions of Monotheism, Morality, and Sociality as the Goals of Education in Surah Luqman Verses 12–19 - Wayan Gastiadirrijal; Cucu Surahman; Elan Sumarna (Lembaga Yasin AlSys, 2026)
Western educational paradigms, which dominate schooling in many Muslim-majority contexts including Indonesia, tend to prioritize cognitive and material outcomes at the expense of spiritual, moral, and social development, contributing to ethical erosion among youth. This study addresses this gap by deriving Islamic educational objectives from Surah Luqman (verses 12–19) as a holistic framework for cultivating insān kāmil (perfect humans), with particular emphasis on tawḥīd (monotheism), morality, and social responsibility. Employing a qualitative library research method, primary data from the Qur’an and classical and contemporary tafsīr were analyzed using thematic content analysis, while secondary sources consisted of post-2000 literature on Islamic pedagogy. Through coding, categorization, interpretation, and cross-validation, the analysis identifies three interconnected dimensions: tawḥīd as an epistemological core fostering devotion and resilience; morality expressed through filial piety (birr al-wālidayn), gratitude, patience, and humility; and social responsibility operationalized through prayer, amr bi-l-maʿrūf wa-nahy ʿan al-munkar (enjoining good and forbidding evil), and courteous conduct. Reflective analysis underscores the contemporary relevance of these Luqmanic principles for Indonesian pesantren and madrasahs, countering secular individualism by informing integrated cognitive–affective–behavioral curricula. The study concludes that embedding educational aims derived from Surah Luqman within Indonesia’s Merdeka Belajar policy framework can enhance students’ moral resilience and offers a value-based alternative to predominantly secular models. The findings contribute to the applied exegesis of the Qur’an in pedagogy and have implications for future empirical interventions and the development of digital tools for value-based Islamic education.